25 Years of partnership with Karnataka evolving model for sustainable urban water service delivery. - Matsunaga, Akira; Dasgupta, Saugata (Asian Development Bank, 2020)
ADB support to the State of Karnataka started in 1995, with the approval of the Karnataka Urban Infrastructure Development Project, ADBs first urban sector loan in India. Since then, ADB supported programs have expanded across the state through three consecutive urban programs. Around 4 million urban residents have benefited from the programs. The interventions have evolved over time, marking an institutional transformation, adopting a programmatic and inclusive approach to ensure sustainable service delivery in urban Karnataka.